2019
DOI: 10.1097/hcr.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Pulmonary Rehabilitation in COPD

Abstract: Purpose: Adherence to pulmonary rehabilitation (PR) is low. This qualitative study used the PRECEDE model to identify predisposing (intrapersonal), reinforcing (interpersonal), and enabling (structural) factors acting as barriers or facilitators of adherence to PR, and elicit recommendations for solutions from patients with chronic obstructive pulmonary disease (COPD). Methods: Focus groups with COPD patients who had attended PR in the past year were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 41 publications
1
27
1
3
Order By: Relevance
“…Even though adherence was good in this study, poor adherence in the general context of PR is common [ 71 ]. Lifestyle changes, which are part of the PR goals [ 32 ], require a great degree of effort from both clinicians and patients.…”
Section: Discussionmentioning
confidence: 86%
“…Even though adherence was good in this study, poor adherence in the general context of PR is common [ 71 ]. Lifestyle changes, which are part of the PR goals [ 32 ], require a great degree of effort from both clinicians and patients.…”
Section: Discussionmentioning
confidence: 86%
“…The merits of peer support have been highlighted previously 35 but not always prioritised by HCPs who often favour symptom management and clinical outcomes. 36 Peer support has been found to sustain change in health behaviours 37 and patients’ engagement with self-management. 30 Consensus from our study demonstrates that patients benefit from peer support, but it is unclear whether one-to-one self-management programmes or a group format are most beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important consideration when designing alternative interventions to address barriers to activity promotion strategies. One of the barriers to conventional pulmonary rehabilitation is the time commitment, both the amount of time required to travel to attend in-person sessions and the amount of time required to complete the rehabilitation sessions [ 29 , 30 ]. Presumably, time is less of a burden for a web-based intervention that does not require travel or in-person sessions, although we still found that age was positively associated with believing it was easy to find time to use the website.…”
Section: Discussionmentioning
confidence: 99%